Citi.gen Z+: the citizens of tomorrow - Maragkaki, A.; Oikonomopoulou, N.; Panigyraki, D.; Argyri, P. (Open Schools Journal for Open Science, 2020)
The name of our project is CITI.GEN Z+. The word citi.gen is a combination of citizen and generation, Z is the number of our generation and + refers to all the future ones. We chose this name because it fully expresses our cause, which is to help the members of the new generations become the global citizens of tomorrow. An overview of global challenges of our world, leads to a basic question ‘How citizens are we?’ and more specific ‘How citizens are the next generation’. In those terms, we design a research to measure the impact in attitudes of global problems to our school community. The methodology based on qualitative and quantitative analysis. As expected, results of this project are the change of the youth’s mentality on matters that affect everyone’s future. We have decided to put together a team of professionals that will help adolescents get through issues they might be faced with and in general aid them in improving their lifestyle. With the passage of time, this “club” will expand and hopefully support all the kids in need. This way, we will create a society where citizens are informed and activated to ameliorate the future.